2013
DOI: 10.5039/agraria.v8i2a1444
|View full text |Cite
|
Sign up to set email alerts
|

Chuva mensal provável para o Agreste de Pernambuco

Abstract: RESUMOO conhecimento da distribuição e da variabilidade temporal da chuva de uma região, é de grande importância, principalmente no Nordeste do Brasil (NEB), na qual este elemento meteorológico é determinante para distinguir dois períodos pluviométricos: o seco e o chuvoso. Desta forma, a chuva exerce grande influência nas atividades agrícolas condicionando a época de plantio e afetando a produtividade dos cultivos. No presente trabalho foram analisadas as distribuições de probabilidade experimental e teórica,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
1
4
0
2
Order By: Relevance
“…The standard deviation varied from a minimum value of 2.7 mm in July to a maximum of 108.6 mm in January. The major values of standard deviation occurs in the rainy period, and that same kind of behavior was verified by SILVA et al (2013b) in the study of the probable rain for the Agreste of Pernambuco, in the rainy period it was observed the major values of standard deviation, indicating great variation on the values of rain in a same month of the year. This way, from the statistical point of view, the fluctuations on the rain values is a sign that the adoption of the monthly average rain for the agricultural planning is not effective in the region.…”
Section: Print-issn 1983-6325 (On Line) E-issn 1984-7548supporting
confidence: 70%
See 1 more Smart Citation
“…The standard deviation varied from a minimum value of 2.7 mm in July to a maximum of 108.6 mm in January. The major values of standard deviation occurs in the rainy period, and that same kind of behavior was verified by SILVA et al (2013b) in the study of the probable rain for the Agreste of Pernambuco, in the rainy period it was observed the major values of standard deviation, indicating great variation on the values of rain in a same month of the year. This way, from the statistical point of view, the fluctuations on the rain values is a sign that the adoption of the monthly average rain for the agricultural planning is not effective in the region.…”
Section: Print-issn 1983-6325 (On Line) E-issn 1984-7548supporting
confidence: 70%
“…The Normal distribution adjusted to the monthly precipitation in the humid period in Táchira, Venezuela, with the application of the adherence test χ 2 at 5% of significance (LYRA et al, 2006). In the climate conditions of Pesqueira in the Agreste of Pernambuco, through the application of the adherence test χ 2 at 5% of significance, the Normal distribution adjusted to the rain data in the months of May, June and August (SILVA et al, 2013b).…”
Section: Print-issn 1983-6325 (On Line) E-issn 1984-7548mentioning
confidence: 99%
“…déficit hídrico. Conforme Silva et al (2013), a precipitação média da região é de 671,90 mm. Em 2013, a precipitação acumulada foi de 320,30 mm e a evapotranspiração potencial de 930,60 mm até o dia 31 de maio, enquanto que no ano de 2012 o total para o mesmo período foi de 895,90 mm.…”
Section: D) Avaliação Do Desempenho Do Modelounclassified
“…Pernambuco State (Brazil) semiarid was classified as one of the driest zones, with an accumulated annual rainfall of 571 mm. The occurrence probability of monthly rainfall distribution in Pesqueira municipality (Pernambuco State; the same region adopted in this study), based on an observed time series from 1920 to 2010 [35]. The mean rainfall from February to July was 84.60 mm month −1 (hydrological year in the region).…”
Section: Introductionmentioning
confidence: 99%